Religionens rolle i naturvidenskabens legitimering - Riis, Ole (Religionsvidenskabeligt Tidsskrift, 1989)
The great sociologist, R.K. Merton, presented in 1938 a study concerning the establishment of science in 17th century England. In this study, he pointed out the importance of Puritanism in the legitimation of natural science. The present essay argues that the establishment of empirical science was an international trend which therefore ought to be seen in an international perspective. Many international and English intellectual sources can be traced. They merged into a mainline during an era when society underwent fundamental changes: the political system changed with the bureaucratization of the monarchical government. The economic system changed with the rationalization of trade and manufacture. These trends also implied an interest in a more pragmatic and materialistic approach to natural phenomena. But the political and economic factors were insufficient for the establishment of natural science in the 16th and 17th centuries. The whole world view was legitimated by religion, including the political power. Therefore, natural science had to demonstrate that it was meant for the honour of God and the benefit of mankind. However, Merton narrows the scope too much, since he focuses on the Puritans. The term is not well-defined, and the discussion therefore becomes either too broad, including all devout Protestants, or too narrow, for instance, by including only non-conformist Presbyterians. The pioneers of natural science were often keenly interested in theology as well. The most important scientists tended to correspond with the church policy of the political leaders, but few of them can be regarded as Presbyterians. During the interregnum, many of the spokesmen of science had close contact with Cromwell. During the restoration, most of the spokesmen of science were Latitudinarian Anglicans. In some cases the religious attitudes swung in accordance with the official church policy. This does not mean that the spokesmen of science were compromising. They were rather representatives of an intellectual élite, which changed its religious views due to the experiences of the civil war, the interregnum and the restoration. A more profound study of the religious writings of the spokesmen of science indicates that they were not typical Puritans in the more narrow Presbyterian sense. Their views were characterized by Natural Theology, tolerant deism and Latitudinarianism. This tendency became more explicit after the Restoration, and the establishment of The Royal Society. Natural Theology was the cornerstone in the comprehensive World View, which also included Natural Law and Natural Science. The outline of the complex was already sketched in the works of the scientific pioneers in the beginning of the 17th century. At the end of the century, it unfolded as the basis for legitimating the Second Revolution. The views of Newton, Locke and Tillotson thus fitted into a universal system. Still the religious legitimation of science was needed. The split between science, religion and politics only took place in the 19th century with the advent of Positivism.